Domain configuration and domain switching in Dy-doped 0.72PMN-0.28PT Piezoceramics with high d33 coefficient. Issue 16 (15th August 2022) - Han, Fuxuan; Qin, Yalin; Zhang, Yongcheng; Yan, Peikun; Wang, Yaqi; Guo, Pengkun; Li, Feng
Abstract: The PMN-28PT- x Dy ( x  = 0, 1, 2, 3 and 4%) piezoelectric ceramics were prepared by the two-step sintering method. A high piezoelectric coefficient d 33 ∼ 1270 pC/N is achieved when x  = 3%. As the Dy doping content increases, the domain configuration transforms from ordered stripe-domains to disordered watermark-domains, while the average domain size decreases evidently from ∼635 nm to ∼100 nm. The domain switching was investigated through strain curves and ferroelectric hysteresis loops measured at different electric field amplitudes and frequencies. To fully polarize the PMN-28PT- x Dy ceramics, the electric field amplitude was found better be higher than 2.5 E c . If pole the ceramics under a. c. electric field of 3 E c, the electric field frequency had better not exceed f 2 . In general, the rare-earth Dy doping has significant effect on domain configuration and domain switching as well as the piezoelectricity.